Answer:
(-3, -3)
Step-by-step explanation:
1.) Rewrite the second equation so 3y is on one side of the equation:
3y=6+5x
2.) Substitute the given value of 3y (replacing 3y with 6+5x, since we know they equal each other) into the equation 17x=-60-3y
Should end up with this:
17x=-60-(6+5x)
3.) Solve 17x=-60-(6+5x)
Calculate Difference: 17x=-66-5x
Combine Like Terms: 22x = -66
Divided both sides by 22 to isolate and solve for x: -3
So We know x=-3, now we got to find the y value. We can use either the first or second equation to find y value, so lets use the second.
3y=6+5x
1.) We know that x=-3, so we can simply substitute x in the equation
3y=6+5x with -3
3y=6+5(-3)
2.) Solve 3y=6+5(-3)
Combine Like Term: 3y=6+-15
Combine Like Term Even More: 3y= -9
Divide by 3 on both sides to isolate and solve for y: y=-3
So now we know y=-3 and once again we know x=-3, so if we format that
(-3,-3)
^ ^
x y
Answer:
288 oz
Step-by-step explanation:
Answer:
Divisor
Step-by-step explanation:
Because the dividend is what you want to get divided by the divisor
76 is the mean for this problem
Each floor is 3.35 feet taller than each floor of the Aon Center